In Television Broadcast Content, Violations Of Privacy Rights Are Reviewed Based On Law Number 32 Of 2002 Concerning Broadcasting And Law Number 27 Of 2022 Concerning Personal Data Protection - Annisa Rami Rivani Israwan; Danrivanto Budhijanto; Prita Amalia (KRTHA BHAYANGKARA, 2024)
This research aims to analyze the legal protection of personal data subject rights in television broadcast content against violations of privacy right based on Law Number 32 of 2002 concerning Broadcasting (Broadcasting Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The approach method used in this research is normative juridical. The data used is primary and secondary data. The collected data is then analyzed using a qualitative juridical method. The result of this research shows that broadcast programs that exploit private life by broadcasting personal information of objects in their content without first providing clear information about the purpose and use of the personal data can be defined as an indicator of privacy violation in television broadcast content when linked to the rights of personal data subjects based on the PDP Law. In addition, legal protection of personal data subject rights in television broadcast content against violation of privacy right is designed to provide legal certainty to personal data subject in television broadcast content. Victims of privacy violation in television broadcast content who are data subject now have their right strengthened, including the right to sue and receive compensation.